BIOTECHNOLOGICAL AND ENVIRONMENTAL EDUCATION POTENTIAL OF Inga edulis Martius: SEED COLLECTED IN THE AMAZON - BRAZIL: Potential of Inga edulis seeds - André Vilhena de Oliveira; Maurício Kersting; Adilson Ben da Costa; Rosana de Cassia de Souza Schneider (BIOTROPIA, 2024)
Article highlights- Inga edulis offer potential for biotechnological and environmental applications.- High protein and carbohydrate content in seeds support diverse agro-industrial uses.- edulis seeds enhance environmental education via forest nurseries schools.- Biotechnological potential of I. edulis seeds extends to ecosystem services. AbstractInga edulis Martius is a native species of the Amazon Forest with great potential for urban afforestation in the cities of the Brazilian Amazon and widely used for the recovery of degraded areas. It is commonly cultivated by the Amazonian population for its edible fruit, quality wood, and excellent agroforestry components. This study aimed to select the matrices and obtain information about the behavior of the seeds in terms of drying, biometry, purity and germination, and chemical composition. The seeds collected in the environmental education action were recognized about potentialities of use for biotechnological products and environmental protection. The seed exploitation of this species is attractive due to its composition (protein and carbohydrates) and forest integration. I. edulis seedlings in the schools contribute to environmental education as a sustainable practice with biotechnological potential for the Amazon region.